Targeting Ameloblatoma into Apoptosis - Ferry Sandra (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Generally ameloblastoma is a locally aggressive, slow growing, non-metastatic epithelial odontogenic benign tumor. However, rarely some ameloblastoma can metastasize in spite of a benign histologic appearance. Targeting ameloblastoma by inducing it into apoptosis could be a beneficial strategy, since many ameloblastoma cases were reported recurrent after surgical therapy.CONTENT: To investigate ameloblastoma in cellular aspect,cytological pattern of ameloblastoma was divided intoouter layer/peripheral and inner layer/central cells. Tumor necrosis factor (TNF)-α, Fas ligand (FasL), TNF receptor (TNFR)1/death receptor (DR)1, TNFR2/DR2, DR4, DR5andFas were highly expressed in central than peripheral cells. Despite inducing apoptosis, TNF-α can induce PI3K leading to Akt and p44/42 mitogen-activated protein kinases (MAPK) activation in AM-1 cells, which later induce cell survival and proliferation. Therefore apoptotic induction in ameloblastoma should be suggested in higher TNF-α concentration. Expression of FasL and Fas are closely associated with squamous metaplasia and granular transformation of the tumor cells, suggesting that apoptosis induced by FasL may play a role in the terminally differentiated or degenerative ameloblastoma cells. TNF-related apoptosis-inducing ligand (TRAIL) has emerged as an apoptotic inducing anticancer agent in tumor cells specifically. TRAIL induced activation of caspases, lowering mitochondrial membrane potential, high number of apoptotic cells in ameloblastoma cells. Therefore, TRAIL could be a potential agent for targeting ameloblastoma, although further study should be explored.SUMMARY: Targeting ameloblastoma by inducing it into apoptosis could be achieved effectively, although some criteria should be considered. Therefore understanding the underlying apoptosis signaling pathways are necessary for inducing ameloblasotma into apoptosis. Investigations on other apoptosis-related molecules, potential apoptosis-inducing natural products, and novel approach in reprogramming, are important in the future for a better anagement of ameloblastoma.KEYWORDS: ameloblastoma, apoptosis, TNF, Fas, TRAIL, Akt, MAPK, caspase